2023
DOI: 10.1111/jipb.13440
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying the toxicity and detoxification of trace metals and metalloids in plants

Abstract: Plants take up a wide range of trace metals/metalloids (hereinafter referred to as trace metals) from the soil, some of which are essential but become toxic at high concentrations (e.g., Cu, Zn, Ni, Co), while others are non-essential and toxic even at relatively low concentrations (e.g., As, Cd, Cr, Pb, and Hg). Soil contamination of trace metals is an increasing problem worldwide due to intensifying human activities. Trace metal contamination can cause toxicity and growth inhibition in plants, as well as acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(26 citation statements)
references
References 294 publications
(404 reference statements)
1
25
0
Order By: Relevance
“…When plants are subjected to heavy metal stress, the elongation growth of their roots is firstly inhibited, followed by their shoot height and dry weight [ 4 ]. In this research, the Pb treatment had no significant effect on the shoot height of M. cordata , while 100 and 200 μmol·L −1 Zn caused a significant decrease in the shoot height.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When plants are subjected to heavy metal stress, the elongation growth of their roots is firstly inhibited, followed by their shoot height and dry weight [ 4 ]. In this research, the Pb treatment had no significant effect on the shoot height of M. cordata , while 100 and 200 μmol·L −1 Zn caused a significant decrease in the shoot height.…”
Section: Discussionmentioning
confidence: 99%
“…Zn-induced ROS were produced and antioxidant enzymes decreased in the roots of the hyperaccumulating ecotype of S. alfredii [ 13 ]. It was also reported that the translocation of heavy metals from the roots to shoots was a detoxification pathway to reduce the stress toxicity to the plant roots [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Together, these results indicate a high consumption of the sugar substrate required for growth. At the cellular level, plants can feature a range of detoxification mechanisms that activate to prevent the accumulation of toxic HM concentrations within the cell, such as the involvement of the plasma membrane in reducing the uptake of HM; chelation in the cytosol by ligands, resulting in complex formation; or the transport of HM/HM complexes to vacuoles [ 21 ]. In this study, the plasma membranes of the B. cordata cells, as a detoxification mechanism, may have reduced the uptake of Cu and Mn since HM accumulation greatly increased under the first concentration tested, followed by a slight increase that plateaued as the concentration increased.…”
Section: Discussionmentioning
confidence: 99%